The Civil Law Tradition, the Pinochet Constitution, and Judge Eugenio Valenzuela - Verdugo, Sergio (Cambridge University Press, 2021)
The depersonalization of the courts encouraged by the civil law tradition makes it less likely that judges in those types of jurisdiction will become towering or, at least, makes their influential jurisprudence anonymous or less visible. By exploring the experience of Eugenio Valenzuela, a Chilean judge who served on the Constitutional Court in the 1980s, this chapter shows that, despite the limitations of the civil law tradition, sometimes it is nonetheless possible to identify a towering judge in a civil law country. The author studies how Valenzuela led a group of judges within the Chilean Constitutional Court and succeeded in challenging critical pieces of legislation enacted by the military Junta during the Pinochet dictatorship. By showing how the Valenzuela jurisprudence helped to advance the transition to democracy against the interests of the authoritarian regime, the chapter claims that founding moments in fragile institutional settings of civil law countries may provide an opportunity for a political towering judge to emerge.
Keywords: 56 Ciencias Jurídicas y Derecho::5605 Derecho y legislación nacionales::5605.07 Derecho público; ODS 16 - Paz, justicia e instituciones sólidas; towering judge; civil law tradition; Eugenio Valenzuela; Chilean Constitutional Court